Proposed new interior design scheme of Ibanez Guitar Center for Bently Music Sdn. Shd. at Lot 4-01, 4-02, 4-03, Second Floor Annexe Gallery, Central Market, Jalan Hang Kasturi 50470, Kuala Lumpur / Farah Nur Izzati Abd Rahim - Abd Rahim, Farah Nur Izzati (Faculty of Architecture, Planning and Surveying, 2010)
A final year student pursuing a diploma course in Interior Design is required to prepare a final year project. The design of the project should be related closely to current issues or similar to it. The knowledge and skill acquired during the duration of the course should be put to practise and onto the drawing board. This also includes the research, case study, interviewing of clients, designing proposals, preparing art work, preparing presentation drawings, design development and last but not least the final presentation. The proposed product for this project is ‘Ibanez’. The idea to propose this project based on market situation about the music instrument business that have been increased and the brand Ibanez have been the popular brand among musicians .Thereafter, a plan was proposed to prepare a retail design that may interest and fulfil the public demand, needs for both of client and customers. From the research and observation conducted on the product and the site, the information and details gathered was used as a guideline to prepare the design. After scouting for a while, 3 lot of gallery at Annexe Central Market was chosen as a proposed site for this project The objective was to design and prepare a music center with the concept and style best suited to the client Bently Music Sdn. Bhd. It is sincerely hoped that the proposed design would give the premise the desired image projection that is needed to enhanced the interest of the Ibanez user.